Economic profitability of crop rotation systems in the Caiuá sandstone area - Volsi,Bruno (2020)
ABSTRACT: Even in areas of predominance of Caiuá sandstone, with soils of low natural fertility that are highly susceptible to erosion and degradation processes, farmers have adopted systems with little diversification, because they believe that they provide a greater economic return. However, agricultural practices such as crop rotation can bring agronomic benefits in terms of conservation agriculture, in addition to economic gains, circumventing edaphoclimatic difficulties in the region. In this context, the objective of this study is to verify whether no-till crop rotation systems are economically profitable, in a Caiuá sandstone area in the northwest region of the Brazilian state of Paraná. To this end, an experiment was conducted in the municipality of Umuarama, state of Paraná, in the crop year 2014/15 to 2016/17. The experimental design used random blocks, with four treatments and four repetitions. The treatments consisted of four crop rotation systems, involving wheat, black oats, canola, safflower, rye, crambe, beans, maize, fodder radish, soybean, sorghum, lupin beans, buckwheat, and triticale cultivars. Crop yields, operating costs, income, and net farm income were assessed. From the results, it was reported that the highest income was obtained in the systems that adopted the largest number of winter and summer commercial crops. Only one treatment was profitable, that is, it had a positive net farm income. This scenario may be associated with the fragility of the region’s soil, which having low fertility, requires a high investment in fertilization and liming to ensure adequate production.